2004
DOI: 10.1111/j.1365-2362.2004.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption is increased relative to work rate in patients with McArdle's disease

Abstract: There is an increased rate of rise in VO2 relative to work rate during exercise in patients with McArdle's disease. There is also a greater rise in catecholamines, which may be the result of a physiological response to substrate starvation, and is likely to contribute to the increase in VO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
4
23
1
Order By: Relevance
“…They concluded that the low RER was due to the lack of release of CO 2 stores due to the absence of lactate acidosis impairment of mitochondrial respiration. Similar results have been reported in groups of McArdle's patients, such that the increased ratio of O 2 consumption to CO 2 production showed the inverse of an anaerobic threshold (105,220,226). These results are similar to those seen in subjects whose leg cycling muscles have been reduced of glycogen prior to performing a progressive exercise test.…”
Section: Menopausesupporting
confidence: 90%
See 2 more Smart Citations
“…They concluded that the low RER was due to the lack of release of CO 2 stores due to the absence of lactate acidosis impairment of mitochondrial respiration. Similar results have been reported in groups of McArdle's patients, such that the increased ratio of O 2 consumption to CO 2 production showed the inverse of an anaerobic threshold (105,220,226). These results are similar to those seen in subjects whose leg cycling muscles have been reduced of glycogen prior to performing a progressive exercise test.…”
Section: Menopausesupporting
confidence: 90%
“…The increased VE versus VCO 2 slope, as well as an increased VE and VE/VCO 2 slope at peak exercise in McArdle's patients led O'Dochartaigh et al (220) to suggest that the catecholamine excess may partially explain their increased ventilatory response to exercise, in agreement with a previous suggestion arising from research in normal individuals (349). The VE/VCO 2 slope provides an indication of the sensitivity of chemoreceptors drive to ventilate.…”
Section: Menopausementioning
confidence: 73%
See 1 more Smart Citation
“…This has been supported in other publications. 1,7,8 More recent literature supports the concept of there being few adverse effects during pregnancy and subsequent labour thus suggesting that labour and vaginal delivery are not precluded. 1 Perez et al and Maté-Muň oz et al report that adults with McArdle disease can re-condition their fitness with pre-exercise sucrose administration 9 and that training is possible under controlled conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Biochemical inefficiency may also result in peak V O 2 Ͼ peak work, such as in McArdle disease, where there is a higher V O 2 for a given amount of work, due to altered substrate utilization and a greater cardiovascular response to exercise. 29 Both mechanical and biochemical factors may explain why different levels of work are achieved for the same peak V O 2 depending on the exercise protocol. For example, total work achieved is higher with a greater work increment protocol, as seen here.…”
Section: Discussionmentioning
confidence: 99%